Interdisciplinary approaches to the prehistory of Keros. (31st December 2018) - Renfrew, Colin; Boyd, Michael; Margaritis, Evi
Abstract : First investigated archaeologically in 1963, it is only with the recent publication of the 2006–2008 excavations that the nature of the Early Bronze Age sanctuary and settlement on Keros is becoming clear. Further investigations – a survey in 2012–2013 and excavations in 2016–2018 – have expanded our knowledge of the sanctuary. This paper sets out the interdisciplinary nature of the research on Keros, highlighting the contribution of a panoply of environmental techniques built into the project methodology from its inception, with all sampling taking place during the excavation itself. In addition, compositional and microscopic analyses of materials such as ceramics, metals and marble contribute to understanding their manufacture and provenance. Finally, taphonomic analyses include micromorphological and soil-chemistry studies, both of which are the largest of their kind yet undertaken in the Aegean. The reflexive contribution of all these specialisms to the ongoing study and publication of the site is described.